Isolation and cultivation as well as in situ identification of MSCs from equine dental pulp and periodontal ligament - Heilen, Laura Beate; Roßgardt, Jessica; Dern-Wieloch, Jutta; Vogelsberg, Jörg; Staszyk, Carsten (Frontiers in Veterinary Science, 2023)
Introduction: The lifelong eruption places a great demand on the dental pulp and periodontal ligament (PDL) of horse teeth. Cells within the pulp and PDL seem to play a key role during this remodeling. Methods: In this study, we isolated and cultivated cells from dental pulp, PDL and retrobulbar fat of four horses. Subsequently, we analyzed them by flow cytometry and immunohistochemistry to determine and compare their characteristics. In addition, we localized these cells within the tissue structure via immunohistochemistry of histological sections. For these analyses, several surface markers were applied. Results: The described method illustrates a feasible approach to isolate and cultivate cells from equine dental pulp and PDL. In the flow cytometry a vast majority of cultivated cells were positive for CD90 and CD40 and negative for CD11a/18, CD45, CD105 and MHCII suggesting that these cells feature characteristics of MSCs (medicinal signaling cells). Immunohistochemistry of histological pulp and PDL sections showed the localization of CD90 positive cells especially in the perivascular region and the subodontoblastic layer. Discussion: Our findings indicate that the isolation and cultivation of MSCs from equine dental pulp and PDL is feasible although an elaborate and complicated harvesting protocol is required. MSCs isolated from dental pulp and PDL are regarded as candidates for new therapeutical approaches in equine dental medicine like regeneration of periodontal lesions, enhancement of periodontal re-attachment after dental replantation and stimulation of pulp-obliteration and apexification in combination with endodontic therapies.